Digital filtering of square signals of chains' vector analizers - D. A. Kondrashov; A. V. Gusinsky; A. M. Kostrikin; M. S. Svirid (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
An algorithm for the use of digital filtering to the sine and cosine components of the quadrature signal in vector network analyzer is presented. Filters used for calibration and measuring stages to the original signals in volts and end measurements values. The mathematical model of three different methods of digital filtering, used together, and allowing better form quadrature signals and remove the noise of various origins in the analyzed signal is presented.